TINJAUAN PEMBERDAYAAN PSIKOLOGIS PADA KARYAWAN CAFE SULTAN di SIDOARJO - Ghurriyah Anissatul; Jati Ratih Kumaya; Maysin Faiqoh Neysthi (Fakultas Psikologi Universitas Wijaya Putra, 2021)
Employees who have good psychological empowerment will encourage their performance results to be better as well. Good psychological empowerment will improve the psychological well-being of employees. Psychological empowerment of employees is needed to improve the quality of the company. The purpose of this study was to find out about the psychological empowerment of the employees of Cafe Sultan Sidoarjo. The methodology used is a qualitative research methodology by conducting interviews with two contract employees of Cafe Sultan Sidoarjo. The results show that Cafe Sultan employees have an impac experienced by cafe sultan employees shows that they have an impact when working at the cafe, self-determination for employees such as freedom to work in their own way is needed so that work can be done with a sense of comfortable but still comply with existing regulations, competence owned by employees is very high and, competence.